Comparative Situation Analysis of Childhood Asthma Incidence in Selected Hospitals Inside and Outside Dhaka City - Nasrin, Nishat; Akter, Ferdowsi; Tithi, Nigar Sultana; Muhammad Asduzzaman, -; Chowdhury, AK Azad (Bangladesh Pharmaceutical Journal, 2020)
Asthma is a common chronic and long-term condition accompanied by coughing, wheezing, chest tightness and breathlessness and affects mainly the lungs. This study was aimed to explore the prevailing situation of asthma among the paediatric patients and its management inside and outside Dhaka city. The study was conducted on 420 asthma patients inside (n = 210) and outside (n = 210) Dhaka. Data were collected using a structured questionnaire from patients or their parents, during the period of January 2015 to June 2015. Most of the patients inside Dhaka reported that their children had frequent asthma attack than outside Dhaka (p<0.001). Wheezing symptoms were also high in Dhaka (p<0.001). We observed better management of the disease inside Dhaka as compared with outside (p<0.001). However, no seasonal variation in terms of exacerbations of symptoms was seen. Moreover, despite greater incidence of childhood asthma in Dhaka city, its management was better here. Mass awareness among parents regarding the incidence and the necessity of continuation of medication as per the advice of physicians are mandatory to reduce the occurrence. Bangladesh Pharmaceutical Journal 23(1): 32-38, 2020